Prevalence of alcohol and tobacco use among Brazilian adolescents: a systematic review - Valter Cordeiro Barbosa Filho; Wagner de Campos; Adair da Silva Lopes
OBJECTIVE: To analyze alcohol and tobacco use among Brazilian adolescents and identify higher-risk subgroups. METHODS: A systematic review of the literature was conducted. Searches were performed using four databases (LILACS, MEDLINE /PubMed, Web of Science, and Google Scholar), specialized websites and the references cited in retrieved articles. The search was done in English and Portuguese and there was no limit on the year of publication (up to June 2011). From the search, 59 studies met all the inclusion criteria: to involve Brazilian adolescents aged 10-19 years; to assess the prevalence of alcohol and/or tobacco use; to use questionnaires or structured interviews to measure the variables of interest; and to be a school or population-based study that used methodological procedures to ensure representativeness of the target population (i.e. random sampling). RESULTS: The prevalence of current alcohol use (at the time of the investigation or in the previous month) ranged from 23.0% to 67.7%. The mean prevalence was 34.9% (reflecting the central trend of the estimates found in the studies). The prevalence of current tobacco use ranged from 2.4% to 22.0%, and the mean prevalence was 9.3%. A large proportion of the studies estimated prevalences of frequent alcohol use (66.7%) and heavy alcohol use (36.8%) of more than 10%. However, most studies found prevalences of frequent and heavy tobacco use of less than 10%. The Brazilian literature has highlighted that environmental factors (religiosity, working conditions, and substance use among family and friends) and psychosocial factors (such as conflicts with parents and feelings of negativeness and loneliness) are associated with the tobacco and alcohol use among adolescents. CONCLUSIONS: The results suggest that consumption of alcohol and tobacco among adolescents has reached alarming prevalences in various localities in Brazil. Since unhealthy behavior tends to continue from adolescence into adulthood, public policies aimed towards reducing alcohol and tobacco use among Brazilians over the medium and long terms may direct young people and the subgroups at higher risk towards such behavior.